GENDERED CAREER PRODUCTIVITY AND SUCCESS IN ACADEMIA IN INDONESIA’S ISLAMIC HIGHER EDUCATION INSTITUTIONS (State Islamic University (UIN) of Sunan Ampel Surabaya, 2012)
Career advancement in Indonesian academia is nationally regulated. It, theoretically, provides equal opportunities for men and women to be productive and successful. The purpose of this study is to analyze gender effects on academic career productivity and success. Seven-hundred and fifty questionnaires were distributed randomly to eight Islamic Higher Education Institutions in seven provinces, from which 220 (Men = 57.7%, and Women = 42.3%) respondents returned the questionnaires with an analyzable quality. Descriptive and multivariate analyses are employed for analyzing and presenting the results. The paper argues that women in Islamic Higher Education Institutions are less productive in terms of publications, hold lower academic rank and leadership positions, and earn significantly less than men. It further argues that Islamic Higher Education Institutions should provide specific empowerment for women by, for example, providing support for their continuing education, professional development, and career opportunities.